Evaluation of case series of delayed tularaemia - Karakeçili, Faruk; Akın, Hicran; Torun, Mümtaz Taner; Akalın, Emin Halis; Helvacı, Safiye (International Journal of Research in Medical Sciences, 2017)
Tularemia is a zoonotic disease caused by the gram-negative bacterium Francisella tularensis. Clinical suspicion is extremely important and serology is the gold standard for diagnosis. The oropharyngeal form of tularemia in Turkey takes the form of outbreaks or sporadic cases. Delay in diagnosis is the major factor in complications. Five delayed cases of tularemia in the Marmara region of Turkey are described in this paper between 2009-2015 years. All patients’ diagnoses were confirmed with serology, and all had LAP on their neck regions. The lymphadenopathies persisted despite medical treatment four being excised by Ear Nose and Throat Clinic (ENT). Tularemia must be considered in the evaluation of masses on the neck, particularly in endemic areas. The most important factor in the successful management of tularemia is early initiation of treatment. The risk of suppuration and surgical interventions increases in delayed cases.